A “Matter of Life and Death”? Patterns of Securitisation and Desecuritisation of Food Resilience in Indonesia - I Gusti Bagus Dharma Agastia (JAS (Journal of ASEAN Studies), 2023)
Food self-sufficiency had been a perennial quest for Indonesian administrations. The research explored two questions. First, how have political leaders securitised the self-sufficiency narrative? Second, is the securitisation of food justified? This research examined the “self-sufficiency” narrative across Indonesian governments and charts the patterns in its securitisation and de-securitisation through the lens of just securitisation theory. The research made two arguments. First, the securitisation of food in Indonesia has not always been for the benefit of the nation, but instead, the political elite. The second argument is the securitisation of food in Indonesia is not always justified, and therefore, necessitates further review of policies related to food security. The findings show that the securitisation of food in general to be unjustified. Therefore, the de-securitising food security and returning it to the realm of normal politics should be the immediate goal for Indonesian administrations, in addition to formulating alternative policies not grounded in the self-sufficiency narrative.